Heirloom Hot Pepper Varieties for Florida - Monica Ozores-Hampton (EDIS)
Here is a guide of the popular pepper varieties used in Florida. The popularity was assessed from a survey among seed suppliers, which include Baker Creek Heirloom Seeds, Burpee, High Mowing Seeds, Southern Exposure Seed Exchange, Tomato Grower Supply Company, Seeds of Change, Territorial Seed Company, and My Patriot Supply. When organic seeds were available, the USDA logo was inserted. The relative Scoville rating, which measures a pepper’s pungency, was also included when it was available. This 15-page fact sheet was written by Monica Ozores-Hampton and published by the UF Department of Horticultural Sciences, November 2013.